Human Health Risks Due to Heavy Metals in Carica Papaya (Pawpaw) Irrigated with Waste Water from Abattoir in Ikwiriri Ward - Saria, Josephat; Yohana, Lawi (Nepal Journal of Multidisciplinary Research, 2025)
Background: The abattoir wastes contain numerous pollutants, many of which can inhibit the growth of soil microorganisms, plants, animals, and negatively impact the entire ecosystem. Carica papaya grown around the Ikwiriri abattoir is widely consumed, yet data on heavy metal contamination from abattoir waste is limited. Objective: To assess the levels of selected heavy metals (Cr, Cu, Pb, Cd, and Zn) in carica papaya fruits, and soils around the abattoir in Ikwiriri Ward. Methods: This study measured selected heavy metals in papaya fruits and their soils using Atomic Absorption Spectroscopy equipped with a continuous flow of Vapour Generation Accessory (VGA). Results and Discussion: Metal concentrations in the fruits decreased in the order (mg/kg): Zn (7.155) > Cu (3.376) > Pb (0.558) > Cr (0.447) > Cd (0.196). Estimated daily intake indicated increasing exposure in the sequence Cu < Zn < Cr < Cd < Pb for both adults and children. Hazard Quotients for Cd and Cu exceeded 1 and Hazard Index values (7.2903–7.6973) were above the acceptable limit, indicating notable non-carcinogenic risks. Carcinogenic risk assessment showed Cr levels (1 × 10⁻³ to 1.2 × 10⁻³) and Cd levels (3.8 × 10⁻⁴ to 4.2 × 10⁻⁴) above permissible thresholds, while Pb (2.6 × 10⁻⁵ to 2.8 × 10⁻⁵) remained within acceptable limits. Conclusion: Overall, the findings reveal significant health risks from heavy metal exposure through papaya consumption and emphasize the need for ongoing environmental monitoring, particularly for chromium due to its elevated carcinogenic potential. Novelty: This study will provide the first evidence of heavy-metal contamination and associated human health risks from Carica papaya irrigated with abattoir wastewater, highlighting a previously unexamined pathway of exposure within the local food chain. Future studies could extend this work by studying other food materials in the country.